SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF THE ANALYSIS OF COLOR DESIGNATIONS IN LANGUAGE - Feruza Kodirova (Bright Mind Publishing, 2025)
Color linguistics is a cross-disciplinary field that investigates how color is encoded, conceptualized, and communicated through language. This article outlines the methodological foundations of color linguistics by addressing its interdisciplinary nature, research approaches, and the role of semantics, psycholinguistics, and cultural studies in understanding color terms. We explore the comparative, typological, cognitive, and etymological methodologies that underpin current research, offering a structured framework for future investigations.
Keywords: Color linguistics, color semantics, psycholinguistics, color categorization, etymology of color terms, cross-linguistic analysis, color perception, cultural symbolism.